Preparation method of high nickel ternary positive electrode material

By using liquid-phase lithium replenishment and spray-coating boric acid treatment after low-temperature sintering, the problems of microcracks and uneven coating in high-nickel ternary cathode materials were solved, improving the cycle performance and conductivity of the materials.

CN114220965BActive Publication Date: 2025-01-10GUANGDONG BRUNP RECYCLING TECH CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111317910.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-09
Publication Date
2025-01-10
Estimated Expiration
2041-11-09

AI Technical Summary

Technical Problem

Existing high-nickel ternary cathode materials are prone to microcracks, mass transfer difficulties, and electrolyte intrusion during cycling, resulting in poor cycling performance and uneven coating modification.

Method used

The process involves first sintering porous primary particles at low temperature under lithium-deficient conditions, then replenishing lithium in the liquid phase and coating them with ionic conductors, followed by spray coating with boric acid and tempering to form a uniform ionic conductor coating layer.

Benefits of technology

It improves the material's cycle performance and conductivity, and enhances its capacity and rate performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114220965B_ABST
    Figure CN114220965B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-nickel ternary positive electrode material, comprising mixing LiOH powder with a high-nickel ternary precursor in a molar ratio of (0.6-0.95): 1, performing a first sintering in an oxygen atmosphere, adding a metal oxide to a LiOH solution to obtain a mixed solution, mixing the mixed solution with a primary sintered material in a protective atmosphere, drying and crushing the mixed material, performing a second sintering on the powder material, spraying an atomized boric acid alcohol solution onto the secondary sintered material, and then performing a tempering treatment to obtain a high-nickel ternary positive electrode material. The primary particle size of the material of the invention is relatively uniform, and Li is formed on the surface of the primary particles. 2 MoO 4 , Li 2 WO 4 or Li 2 SnO 3 The plasma conductor coating can protect the material. At the same time, the secondary sphere surface of the material also has an ion conductor Li 3 BO 3 The coating layer also protects the material, that is, both the primary particles and the secondary balls of the material have a coating layer, which greatly enhances the electrical conductivity of the material and improves the capacity, cycle and rate performance of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium-ion batteries, and in particular relates to a method for preparing a high-nickel ternary positive electrode material. Background Art

[0002] High-nickel ternary positive electrode materials mainly refer to NCM ternary materials with a Ni content greater than 60%. As the Ni content increases, the specific capacity of NCM ternary materials will also increase. High-nickel ternary is one of the future development directions of positive electrode materials. Although high-nickel ternary materials have high specific capacity, they also have some disadvantages during use. For example, microcracks are easily generated due to volume changes during the cycle, and there may be large pores between primary particles, resulting in mass transfer difficulties and electrolyte intrusion causing material degradation, etc. These will lead to poor cycle performance of high-nickel ternary materials.

[0003] At present, the substrate sintering and coating modification of commercial high-nickel ternary materials generally adopt the solid phase mixing-high temperature sintering method. Although this method is simple and easy to implement, it also has the following disadvantages: 1) For substrate sintering, it is difficult to ensure that the precursor and the lithium source are fully mixed, resulting in uneven growth of primary particles; 2) For coating modification, it is difficult to ensure the uniformity of the coating layer, which is prone to local over-thickness or no coating, and the coating layer basically only exists on the surface of the secondary ball material. Summary of the invention

[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention provides a method for preparing a high-nickel ternary positive electrode material.

[0005] According to one aspect of the present invention, a method for preparing a high-nickel ternary positive electrode material is provided, comprising the following steps:

[0006] LiOH powder is mixed with a high-nickel ternary precursor in a molar ratio of (0.6-0.95):1, and a first sintering is performed in an oxygen atmosphere to obtain a primary sintered material; the high-nickel ternary precursor is a secondary spherical morphology composed of primary particles.

[0007] A metal oxide is added to a LiOH solution to obtain a mixed solution, wherein the metal oxide is at least one of an oxide of Mo, W or Sn; the mixed solution is Li 2 MoO 4 , Li 2 WO 4 or Li 2 SnO 3 Mixed solution with LiOH;

[0008] Under a protective atmosphere, the mixed solution is mixed with a primary sintering material to obtain a mixed material, the mixed material is dried and crushed to obtain a powder material, and the powder material is subjected to a second sintering to obtain a secondary sintering material;

[0009] The atomized boric acid alcohol solution is sprayed onto the secondary sintered material, and then tempered to obtain the high-nickel ternary positive electrode material.

[0010] In some embodiments of the present invention, the temperature of the first sintering is 500-650° C.; the time of the first sintering is 2-8 hours.

[0011] In some embodiments of the present invention, the concentration of Li in the mixed solution is 10-37 g / L.

[0012] In some embodiments of the present invention, the liquid-to-solid ratio of the mixed solution to the primary sintered material is 0.25-1 mL / g.

[0013] In some embodiments of the present invention, the stirring time is 3-120 min.

[0014] In some embodiments of the present invention, the drying method is vacuum drying.

[0015] In some embodiments of the present invention, the mixing method is mechanical stirring, ultrasonic vibration or a combination of the two.

[0016] In some embodiments of the present invention, the temperature of the second sintering is 700-1000° C.; the time of the second sintering is 8-24 hours; and the second sintering is performed in an oxygen atmosphere.

[0017] In some embodiments of the present invention, the protective atmosphere is nitrogen, oxygen, argon or CO 2 of compressed air.

[0018] In some embodiments of the present invention, the secondary sintered material is a positive electrode material in which primary particles are coated with an ion conductor, and the ion conductor is Li 2 MoO 4 , Li 2 WO 4 or Li 2 SnO 3 At least one of the above, the coating amount of the ion conductor is: based on the total amount of Mo, W and Sn in the ion conductor, it is 0.05-0.8wt% of the secondary sintered material.

[0019] In some embodiments of the present invention, the boric acid alcohol solution is prepared by adding boric acid to an alcohol solution and heating the solution in a water bath to obtain the boric acid alcohol solution; the water bath heating temperature is 50-70° C. Preferably, the alcohol solution is anhydrous ethanol.

[0020] In some embodiments of the present invention, the concentration of B in the boric acid alcohol solution is 15-25 g / L.

[0021] In some embodiments of the present invention, the boron content in the high-nickel ternary positive electrode material is 0.02-0.5wt%.

[0022] In some embodiments of the present invention, the tempering treatment is performed in an oxygen atmosphere; the tempering treatment temperature is 200-350° C.; and the tempering treatment time is 4-12 hours.

[0023] According to a preferred embodiment of the present invention, at least the following beneficial effects are achieved:

[0024] 1. The first sintering of the present invention is carried out in the absence of lithium and at a relatively low temperature. The primary particles are initially formed but do not grow completely, forming a primary sintered material with incomplete growth and porous primary particles, which provides good conditions for subsequent liquid phase secondary lithium supplementation and primary particle coating.

[0025] 2. The present invention places the primary sintered material in a 2 MoO 4 , Li 2 WO 4 or Li 2 SnO 3 In the LiOH solution containing one or more components in the primary sintered material, liquid phase lithium supplementation and primary particle coating are carried out and the water is evaporated. On the one hand, the residual lithium unevenly distributed on the surface of the primary sintered material can be dissolved and put into the solution; on the other hand, LiOH and Li 2 MoO 4 , Li 2 WO 4 or Li 2 SnO 3 The lithium ions will enter the pores of the primary sintered material and deposit during the evaporation process, thereby achieving uniform lithium replenishment and coating of the primary particle surface with ion conductor Li 2 MoO 4 , Li 2 WO 4 or Li 2 SnO 3 One or more of .

[0026] 3. The present invention sprays the sintered material with boric acid and then performs tempering treatment. 3 BO3 Will decompose into B 2 O 3 , B 2 O 3 It is an acidic oxide and reacts with LiOH and Li 2 CO 3 The reaction generates Li 3 BO 3 The excess lithium source is due to the molar ratio of the total lithium source added by the primary lithium supplementation + secondary lithium supplementation to the transition metal element Li / Me>1, and the high-nickel ternary cathode material itself will also have residual lithium on the surface, so that the residual lithium on the surface can react with H 3 BO 3 Reaction, to obtain secondary sphere surface coated with ion conductor Li 3 BO 3 The finished product is obtained, thereby obtaining a finished product with both the primary particle surface and the secondary ball surface coated.

[0027] 4. The primary particles of the high nickel ternary positive electrode material prepared by the present invention are relatively uniform in size and closely bonded to each other. 2 MoO 4 , Li 2 WO 4 or Li 2 SnO 3 The plasma conductor coating can protect the material, and even if the material forms microcracks or cracks along the gaps between the primary particles during the cycle, the coating on the surface of the primary particles can continue to protect the material, thereby improving the material's cycle performance; at the same time, the secondary ball surface of the material also has an ion conductor Li 3 BO 3 The coating layer also protects the material, that is, both the primary particles and the secondary balls of the material have a coating layer, and the coating materials are all ion conductors, which can greatly enhance the electrical conductivity of the material, thereby improving the capacity, cycle and rate performance of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The present invention will be further described below with reference to the accompanying drawings and embodiments, wherein:

[0029] Figure 1 This is a SEM image of the primary sintered material of Example 1 of the present invention;

[0030] Figure 2 This is a SEM image of the secondary sintered material of Example 1 of the present invention;

[0031] Figure 3 This is a SEM image of the finished product of the high-nickel ternary positive electrode material of Example 1 of the present invention;

[0032] Figure 4 This is a 0.5C cycle comparison diagram of materials of different schemes of the present invention;

[0033] Figure 5 This is a comparison chart of the rate performance of materials with different schemes of the present invention. DETAILED DESCRIPTION

[0034] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0035] Example 1

[0036] This embodiment prepares a high-nickel ternary positive electrode material, and the specific process is as follows:

[0037] (1) LiOH and high nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 Mix evenly at a molar ratio of Li:Me=0.8;

[0038] (2) placing the above-mentioned mixture in an oxygen atmosphere and performing a first sintering at 500° C. for 6 hours to obtain a primary sintered material with incomplete primary particle growth and being porous;

[0039] (3) Dissolve a certain amount of LiOH in pure water to prepare a LiOH solution, and then add a certain amount of SnO 2 , fully stirred to prepare a mixed solution A, wherein the Li concentration of the mixed solution A is 32 g / L and the Sn concentration is 7.62 g / L;

[0040] (4) placing the primary sintered material in a sealed container filled with nitrogen;

[0041] (5) Pour the mixed solution A into the primary sintered material at a liquid-to-solid ratio of 0.5 mL / g, and perform ultrasonic vibration for 60 min to obtain a mixed material B;

[0042] (6) Evaporate the mixed material B in a vacuum drying oven at 70°C;

[0043] (7) crushing and sieving the above evaporated material to obtain powder material C;

[0044] (8) The powder material C was sintered for the second time in an oxygen atmosphere at a sintering temperature of 800°C for 16 h to obtain a primary particle.2 SnO 3 Coated secondary sintered material, Li 2 SnO 3 The coating amount is calculated as 0.38wt% of the secondary sintered material in terms of Sn;

[0045] (9) Add a certain amount of boric acid to anhydrous ethanol, heat in a water bath at 70° C. to completely dissolve the boric acid, and prepare a boric acid ethanol solution, wherein the boric acid content in the solution is 20 g / L;

[0046] (10) The secondary sintered material is placed in a high-efficiency mixer for mixing, and then the boric acid ethanol solution is evenly sprayed onto the secondary sintered material through an atomizer, the liquid-to-solid ratio of the boric acid ethanol solution to the secondary sintered material is 0.05 mL / g, and the spraying time is 20 min;

[0047] (11) The spray-coated secondary sintered material is tempered in an oxygen atmosphere at a tempering temperature of 250°C for a holding time of 10 h to obtain a high-nickel ternary positive electrode material. The finished product Li 3 BO 3 The coating amount, calculated as B, is 0.1 wt % of the high nickel ternary positive electrode material.

[0048] Figure 1 This is the SEM picture of the primary sintered material of this embodiment. It can be clearly seen from the picture that the primary particles of the primary sintered material are not fully grown, there are large pores between the primary particles, and the surface of the entire secondary spherical particles is uneven.

[0049] Figure 2 This is the SEM image of the secondary sintered material of this embodiment. It can be seen from the image that after liquid phase secondary lithium supplementation and sintering, the primary particles of the obtained secondary sintered material have obviously grown, the pores between the primary particles have been significantly reduced, and the surface smoothness of the entire secondary spherical particles has been greatly improved.

[0050] Figure 3 This is the SEM image of the finished product of the high nickel ternary positive electrode material of this embodiment. It can be seen from the figure that after H 3 BO 3 After coating and sintering, the primary particles of the finished product are tightly bonded and the surface of the entire secondary ball particles is relatively smooth.

[0051] Example 2

[0052] This embodiment prepares a high-nickel ternary positive electrode material, and the specific process is as follows:

[0053] (1) LiOH and high nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2Mix evenly at a molar ratio of Li:Me=0.9;

[0054] (2) placing the above mixture in an oxygen atmosphere and performing a first sintering at 550° C. for 4 hours to obtain a primary sintered material with incomplete primary particle growth and being porous;

[0055] (3) Dissolve a certain amount of LiOH in pure water to prepare a LiOH solution, and then add a certain amount of MoO 3 , fully stirred to prepare a mixed solution A, wherein the Li concentration of the mixed solution A is 30 g / L and the Mo concentration is 15 g / L;

[0056] (4) placing the primary sintered material in a sealed container filled with nitrogen;

[0057] (5) Pour the mixed solution A into the primary sintered material at a liquid-to-solid ratio of 0.3 mL / g, and stir for 30 min by mechanical stirring to obtain a mixed material B;

[0058] (6) Evaporate the mixed material B in a vacuum drying oven at 90°C;

[0059] (7) crushing and sieving the above evaporated material to obtain powder material C;

[0060] (8) The powder material C was sintered for the second time in an oxygen atmosphere at a sintering temperature of 830°C for 14 h to obtain a primary particle. 2 MoO 3 Coated secondary sintered material, Li 2 MoO 3 The coating amount is calculated as Mo, which is 0.45wt% of the secondary sintered material;

[0061] (9) Add a certain amount of boric acid to anhydrous ethanol, heat in a water bath at 70° C. to completely dissolve the boric acid, and prepare a boric acid ethanol solution, wherein the boric acid content in the solution is 20 g / L;

[0062] (10) The secondary sintered material is placed in a high-efficiency mixer for mixing, and then the boric acid ethanol solution is evenly sprayed onto the secondary sintered material through an atomizer, the liquid-to-solid ratio of the boric acid ethanol solution to the secondary sintered material is 0.04 mL / g, and the spraying time is 15 min;

[0063] (11) The spray-coated secondary sintered material was tempered in an oxygen atmosphere at a tempering temperature of 275°C for 8 hours to obtain a high-nickel ternary positive electrode material. The finished product Li 3 BO 3 The coating amount, calculated as B, is 0.1 wt % of the high nickel ternary positive electrode material.

[0064] Example 3

[0065] This embodiment prepares a high-nickel ternary positive electrode material, and the specific process is as follows:

[0066] (1) LiOH and high nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 Mix evenly at a molar ratio of Li:Me=0.95;

[0067] (2) placing the above-mentioned mixture in an oxygen atmosphere and performing a first sintering at 600° C. for 3 hours to obtain a primary sintered material with incomplete primary particle growth and being porous;

[0068] (3) Dissolve a certain amount of LiOH in pure water to prepare a LiOH solution, and then add a certain amount of WO 3 , fully stirred to prepare a mixed solution A, wherein the Li concentration of the mixed solution A is 21 g / L and the W concentration is 6.31 g / L;

[0069] (4) placing the primary sintered material in a sealed container filled with nitrogen;

[0070] (5) Pour the mixed solution A into the primary sintered material at a liquid-to-solid ratio of 0.6 mL / g, and stir for 10 min by mechanical stirring + ultrasonic vibration to obtain a mixed material B;

[0071] (6) Evaporate the mixed material B in a vacuum drying oven at 110°C;

[0072] (7) crushing and sieving the above evaporated material to obtain powder material C;

[0073] (8) The powder material C was sintered for the second time in an oxygen atmosphere at a sintering temperature of 850°C for 12 h to obtain a primary particle. 2 WO 3 Coated secondary sintered material, Li 2 WO 3 The coating amount is calculated as W, which is 0.38wt% of the secondary sintered material;

[0074] (9) Add a certain amount of boric acid to anhydrous ethanol, heat in a water bath at 70° C. to completely dissolve the boric acid, and prepare a boric acid ethanol solution, wherein the boric acid content in the solution is 20 g / L;

[0075] (10) The secondary sintered material is placed in a high-efficiency mixer for mixing, and then the boric acid ethanol solution is evenly sprayed onto the secondary sintered material through an atomizer, the liquid-to-solid ratio of the boric acid ethanol solution to the secondary sintered material is 0.05 mL / g, and the spraying time is 30 min;

[0076] (11) The spray-coated secondary sintered material was tempered in an oxygen atmosphere at a tempering temperature of 325°C for a holding time of 6 h to obtain a high-nickel ternary positive electrode material. The finished product Li 3 BO 3 The coating amount, calculated as B, is 0.1 wt % of the high nickel ternary positive electrode material.

[0077] Comparative Example 1

[0078] This comparative example prepares a high-nickel ternary positive electrode material, and the specific process is as follows:

[0079] LiOH and high nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 The mixture is mixed evenly at a molar ratio of Li:Me = 1.03, and then kept at 550 ° C for 6 hours in an oxygen atmosphere, and then heated to 810 ° C for 16 hours to obtain the uncoated high-nickel ternary positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O 2 .

[0080] Comparative Example 2

[0081] This embodiment prepares a high-nickel ternary positive electrode material, and the specific process is as follows:

[0082] LiOH and high nickel ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH) 2 The mixture is mixed evenly at a molar ratio of Li:Me = 1.03, and then kept at 550 ° C for 6 hours in an oxygen atmosphere, and then heated to 810 ° C for 16 hours to obtain the high-nickel ternary positive electrode material LiNi 0.8 Co 0.1 Mn 0.1 O 2 Then, LiNi 0.8 Co 0.1 Mn 0.1 O 2 With H 3 BO 3 Mix thoroughly and then keep at 325℃ for 6h in oxygen atmosphere to obtain the secondary ball with H 3 BO 3 Coated high nickel ternary cathode material LiNi 0.8 Co 0.1 Mn 0.1 O 2.

[0083] Test example

[0084] Examples 1-3 and Comparative Examples 1-2 were made into button batteries, and the first cycle specific capacity, first efficiency, and 100-cycle cycle retention rate were tested at 25° C. The test conditions were: 2.8-4.25V, 0.5C charge and discharge, using a LAND charge and discharge instrument, and the test results are shown in Table 1.

[0085] Table 1 Comparison of electrochemical performance of different schemes

[0086]

[0087] As can be seen from Table 1, the electrochemical performance of the high-nickel ternary positive electrode material double-coated with primary particles and secondary balls prepared in the embodiment is significantly better than that of comparative examples 1 and 2.

[0088] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A method for preparing a high-nickel ternary positive electrode material, characterized in that: The following steps are involved: The LiOH powder is mixed with the high nickel ternary precursor in a molar ratio of (0.6-0.95):1, and a first sintering is performed in an oxygen atmosphere to obtain a primary sintered material; Adding a metal oxide to a LiOH solution to obtain a mixed solution, wherein the metal oxide is at least one of an oxide of Mo, W or Sn; Under a protective atmosphere, the mixed solution is mixed with a primary sintering material to obtain a mixed material, the mixed material is dried and crushed to obtain a powder material, and the powder material is subjected to a second sintering to obtain a secondary sintering material; Spraying an atomized boric acid alcohol solution onto the secondary sintered material, and then performing a tempering treatment to obtain the high-nickel ternary positive electrode material; The high-nickel ternary precursor is a secondary spherical morphology composed of primary particles; The temperature of the first sintering is 500-650°C.

2. The preparation method according to claim 1, characterized in that: The concentration of Li in the mixed solution is 10-37 g / L; the liquid-to-solid ratio of the mixed solution to the primary sintered material is 0.25-1 mL / g.

3. The preparation method according to claim 1, characterized in that: The temperature of the second sintering is 700-1000° C.; the second sintering is performed in an oxygen atmosphere.

4. The preparation method according to claim 1, characterized in that: The protective atmosphere is nitrogen, oxygen, argon or compressed air from which CO2 has been removed.

5. The preparation method according to claim 1, characterized in that: The secondary sintered material is a positive electrode material of an ion conductor coated with primary particles, the ion conductor is at least one of Li2MoO4, Li2WO4 or Li2SnO3, and the coating amount of the ion conductor is: based on the total amount of Mo, W and Sn in the ion conductor, it is 0.05-0.8wt% of the secondary sintered material.

6. The preparation method according to claim 1, characterized in that: The preparation process of the boric acid alcohol solution is as follows: adding boric acid into an alcohol solution and heating the solution in a water bath to obtain the boric acid alcohol solution; the water bath heating temperature is 50-70°C.

7. The preparation method according to claim 1, characterized in that: The concentration of B in the boric acid alcohol solution is 15-25 g / L.

8. The preparation method according to claim 1, characterized in that: The boron content in the high-nickel ternary positive electrode material is 0.02-0.5wt%.

9. The preparation method according to claim 1, characterized in that: The tempering treatment is carried out in an oxygen atmosphere; the temperature of the tempering treatment is 200-350°C.

Citation Information

Patent Citations

  • Nickel-cobalt-manganese ternary positive electrode material and preparation method and application thereof

    CN112499695A

  • Method for repairing surface structure of high-nickel positive electrode material, high-nickel positive electrode material obtained therefrom, and lithium ion battery

    WO2021114746A1